PRIORITY COMPETENCIES OF A MODERN TEACHER OF A HIGH SCHOOL - Kartushina, Natalya (Revista Inclusiones, 2021)
The article is devoted to the challenging problem of a competence-based approach in the higher education system of the Russian Federation. The object of the research is the competence of a foreign language teacher in higher education. The subject of the research is the emergence of new competencies that ensure the modern quality of the educational process that meets the needs of socio-economic growth. Based on the analysis of existing and recognized competencies of a foreign language teacher, as well as trends in the growth of teacher’s professionalism, the authors propose to introduce the following competencies into the description of professionalism: research, organizational and managerial and reflective, which will remain relevant in the nearest future of social development. Methods of formal logic, deduction and analysis are used in the research. The results obtained make it possible to form the competence matrix of a modern teacher of a foreign language in higher education. The proposed competencies describe both the intellectual and psychological qualities of the teacher and knowledge, skills and abilities. The use of these competencies, according to the authors, will increase the effectiveness of teachers and, ultimately, the educational process of higher education.